(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. La circolare misteriosa - 3. Sulla presunta “forza normativa” di una circolare - 4. Vedere il proprio nome su una tomba: un problema “giuridicamente irrilevante”? - 5. Il sonno della ragione genera mostri. About the ‘scarlet letter’: A ‘legally irrelevant’ problem? Some considerations ABSTRACT: The contribution, stimulated by a rebuttal article, delves into the issue of the unsolicited burial of foetuses; it reconstructs the research work on the Cattin Circular, which founds the moral duty of such burial. The Circular cannot be found at the Ministry of Health itself.